1999
DOI: 10.1080/003655299750025480
|View full text |Cite
|
Sign up to set email alerts
|

24-h Recording of Intragastric pH: Technical Aspects and Clinical Relevance

Abstract: van Herwaarden MA, Samsom M, Smout AJPM. 24-h recording of intragastric pH: technical aspects and clinical relevance. Scand J Gastroenterol 1999;34 Suppl 230:9-16.Background: Information about gastric acid secretion and gastric acidity can be obtained using several techniques but, presently, continuous intragastric pH recording is probably the one applied most frequently. This paper aims to review the technical aspects and some important applications of intragastric pH monitoring in research and clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 61 publications
4
25
0
Order By: Relevance
“…The effect is dual and results from the interaction between the existing basic food moieties and the acids released in the stomach (31,40), as well as from the hydrolysis of proteins by pepsin, with concurrent release of amines. This buffering effect was evidenced in the present study when gastric challenge was carried out under static conditions, with no pH adjustment, and resulted in a moderate decrease of acidity.…”
Section: Discussionmentioning
confidence: 99%
“…The effect is dual and results from the interaction between the existing basic food moieties and the acids released in the stomach (31,40), as well as from the hydrolysis of proteins by pepsin, with concurrent release of amines. This buffering effect was evidenced in the present study when gastric challenge was carried out under static conditions, with no pH adjustment, and resulted in a moderate decrease of acidity.…”
Section: Discussionmentioning
confidence: 99%
“…They can be connected to a recording device directly, or indirectly by radiotelemetry. 40 The positioning of the electrode is vital as different parts of the stomach may have different pH. Fackler et al demonstrated that positioning the probe in the fundus was the optimal position for measurement of gastric pH, whereas Cilluffo et al showed in postprandial states pH measurement in the antrum was more dependable.…”
Section: -38mentioning
confidence: 99%
“…Hence, some concerns have been raised in using pH values as a measure of gastric acid. 40 It should be borne in mind that gastric pH neither gives a quantitative evaluation of the volume of acid secretion nor does it necessarily correlate to gastric acid secretion as several factors like food, gastric emptying, bicarbonate secretion, dilutional effect of saliva and intestinal secretions can all influence the pH of gastric liquid.…”
Section: -38mentioning
confidence: 99%
“…Thus, gastric pH measurement provides important pharmacodynamic information regarding the efficacy of anti-secretory medications like ranitidine. 18 In a study of infants, ranitidine 2 mg/kg/dose administered every eight hours was more effective than 2 mg/kg, 3 mg/kg or even 4 mg/kg administered every 12 hours in terms of total time with gastric pH values < 3 and < 4. 19 In another infant study, ranitidine 5 mg/kg/dose orally increased gastric pH for 9-10 hours.…”
Section: Discussionmentioning
confidence: 99%